Selecting haematological malignancy patients for intravenous immunoglobulin. Issue 10 (October 2016) - Paxton, L.; Hawkins, C.; Crispin, P.
Abstract : Prior randomised studies of immunoglobulin replacement therapy have studied mixed populations with or without a history of infections. Immunoglobulin therapy is expensive and in limited supply suggesting that optimising patient selection is of value. In this retrospective study, infection history identified high‐risk groups benefiting from treatment. A group of patients without any infection history had a low risk of infection without immunoglobulin.